Linking Social Media Marketing and Brand Loyalty: The Mediating Role of Brand Gestalt - Queenditya, Sewow Cleopatra; Lovely, Lengkong Beatrix; Mandagi, Deske W. (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study investigates the relationship between social media marketing (SMM), brand gestalt, and brand loyalty. Using a quantitative survey, this research focuses on customers of the online store VictoriaThings. A convenience sampling method was employed, resulting in 265 participants in the survey. After confirming validity and reliability, structural equation modeling (SEM) was used to analyze the hypotheses. The findings reveal a significant relationship between SMM and the four dimensions of brand gestalt (Story, Sensescape, Servicescape, and Stakeholder). Additionally, the dimensions of Sensescape, Servicescape, and Story within the brand gestalt framework emerged as significant predictors of Customer Loyalty. This study offers valuable insights for businesses aiming to develop effective social media marketing strategies that leverage brand gestalt to enhance brand loyalty and achieve strategic goals.